Isolation, purification, and phenotypic characterization of virulent Klebsiella pneumoniae phages from environmental samples in Addis Ababa, Ethiopia: A synergistic approach combining spot assay and streak plating - Assefa Asnakew Abebe; Alemayehu Godana Birhanu; Tesfaye Sisay Tessema (PLoS ONE, 2025)
Background Multidrug-resistant (MDR) Klebsiella pneumoniae poses a significant global health threat, necessitating alternative therapies like bacteriophage treatment. Traditional phage isolation methods, such as plaque assays, are resource-intensive and thus limit large-scale screening. This study aimed to isolate and purify phages targeting MDR K. pneumoniae using a combined spot-streak plating method and to compare its efficiency with conventional techniques. Materials and methods A total of 62 environmental samples were screened against two MDR K. pneumoniae isolates using a combined approach: initial phage detection by spot assays followed by streak plate-based purification for isolating pure phage clones. Traditional plaque assays were also performed for comparison. Isolated phages were characterized by performing host range analysis against 45 bacterial isolates and determining their burst size. Additionally, their stability was assessed across various pH and temperature conditions, and single-step growth curve experiments were conducted. Results The combined spot assay and streak plate purification method yielded 22 phages, whereas plaque assays isolated 17 phages. Eight phages with high titers and lytic activity were selected for further analysis. These phages exhibited broad host ranges, with two phages lysing up to 55.5% of tested isolates. Stability assays showed effective lytic activity between pH 5 and 9 and temperatures up to 60°C. Single-step growth curves revealed latent periods ranging from 15 to 40 minutes and burst sizes between 76 and 310 PFU per infected cell. The combined method reduced both the isolation time and resource requirements. Conclusion The integration of spot assays with streak plate-based purification provides an efficient and less resource-intensive method for isolating diverse phages targeting MDR K. pneumoniae. The isolated phages demonstrate promising broad-spectrum lytic activity and physiological stability, supporting their potential use in phage therapy. Recommendation Further genomic characterization is necessary to confirm the strictly lytic nature of these phages and to exclude the presence of undesirable genes. Subsequent studies should focus on in vivo efficacy testing and formulation optimization to facilitate clinical application.